Hepatopulmonary Syndrome - Machicao, Victor I.; Fallon, Michael B. (Seminars in Respiratory and Critical Care Medicine, 2012)
Hepatopulmonary syndrome (HPS) is characterized by an oxygenation defect induced by pulmonary vascular dilatation in the setting of liver cirrhosis or portal hypertension. It is defined by an alveolar–arterial gradient > 15 mm Hg measured at sea level. This syndrome is seen in 15 to 30% of cirrhotic patients and has been associated with worse survival. Most HPS patients are either asymptomatic or develop the insidious onset of dyspnea. The key event in its pathogenesis is the development of intrapulmonary vascular dilatation (IPVD), which has been linked to increased pulmonary levels of nitric oxide. Pulse oximetry is a useful screening test for HPS, which can guide subsequent use of arterial blood gases. Contrast-enhanced transthoracic echocardiography is the most effective test to demonstrate IPVD. Another method for detecting IPVD is the radionuclide lung perfusion scanning, using technetium-labeled macroaggregated albumin particles. Liver transplantation is the only available treatment for HPS, resulting in complete resolution or significant improvement in gas exchange in over 85% of patients.
Keywords: hepatopulmonary syndrome; hypoxemia; pulse oximetry; contrast-enhanced transthoracic echocardiography; liver transplantation